2016
DOI: 10.1016/j.anorl.2016.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblastoma of the maxillary sinus in a child presenting with exophthalmos

Abstract: Osteoblastoma of the maxillary sinus is rare. CT assessment must be as precise as possible to avoid confusion with another tumour. The diagnosis can only be confirmed by histological examination. This case report is completed by a review of the literature with description of the main differential diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…Mitotic activity is extremely rare in the stromal cells. 32 Cystic degeneration and secondary aneurysmal bone cyst formation may occur in both variants. 39 Clear histologic distinctions have been made between the 2 variants of JOF; however, Bhuyan et al reported on 1 of 2 known cases of JOF presenting with a rare lesion in the maxilla, in which both histologic variants coexisted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mitotic activity is extremely rare in the stromal cells. 32 Cystic degeneration and secondary aneurysmal bone cyst formation may occur in both variants. 39 Clear histologic distinctions have been made between the 2 variants of JOF; however, Bhuyan et al reported on 1 of 2 known cases of JOF presenting with a rare lesion in the maxilla, in which both histologic variants coexisted.…”
Section: Discussionmentioning
confidence: 99%
“…31 Sinonasal osteoblastomas are extremely rare. 32 Nevertheless, there are a few case reports, such as those by Vella et al and Jaswal et al, who described cases of osteoblastomas in children involving the maxillary sinus and nasal cavities. 32,33 However, osteoblastomas in the paranasal sinuses are quite rare in young children.…”
Section: Differential Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Of these cases, 5 noted that their initial surgery was subtotal with the intended benefit of smaller or less conspicuous incisions or reduced morbidity to nearby critical structures. These included a transoral enuclation, 22 limited transfacial resection, 23 bicoronal incision with craniotomy, 9 and endoscopic piece meal resections. 24,25 The time to recurrence in these cases ranged from 2 to 8 months.…”
Section: Discussionmentioning
confidence: 99%
“…daha çok baş boyun bölgesinde görülürler. Baş boyun bölgesinde frontoetmoid bölgede, maksiller sinüste, mandibulada ve nadiren de temporal kemikte izlenirler (3)(4)(5)(6)(7)(8). Osteom insidansı baş boyun bölgesinde görülen benign tümörler içerisinde %0,1-1 arasında bildirilmektedir (9).…”
unclassified